Absolute Competence in the Fields of Alms in the Religious Courts - Siah Khosyi'ah; Royhan Aziz Ghifari; Mohamad Sar’an; Ah Fathonih (UIN Sunan Gunung Djati Bandung, 2021)
This research aims to investigate the absolute competence in the fields of alms in the Religious Court in Indonesia. The method used in this research is normative juridical research with the type of prescriptive analysis of research, namely studying the purpose of the law, the values of justice, the validity of the rule of law, legal concepts, and legal norms. This research found that the case of alms has never appeared. It can happen because alms cases are resolved through non-litigation. The settlement of alms disputes has likely been completed up to the zakat management institution's level, and alms has become part of Islam's teachings. It is necessary o cooperate with other institutions in resolving it legally. Besides that, there is a need for legislation that provides opportunities to solve alms' problem does not clash with its legal aspects.